Characterization of a unique phosphopantetheinyl transferase (PPTase) in the fish pathogen Pseudomonas plecoglossicida - Yu Chi; Tingting Jia; Jigang Chen; Zhijuan Mao (PLoS ONE, 2026)
Phosphopantetheinyl transferase (PPTase) is a key enzyme that catalyzes 4’-phosphopantetheinylation at conserved serine residues of fatty acid synthases, polyketide synthases, and nonribosomal peptide synthetases. It is involved in the biosynthesis of primary and secondary metabolites and has been well characterized as an important virulence factor in many pathogenic microorganisms. A unique Sfp-type PPTase was annotated in Pseudomonas plecoglossicida NB2011, the causative agent of visceral granulomas syndrome in the large yellow croaker ( Larimichthys crocea ). However, the biological function and virulence significance of this enzyme in the pathogen have not yet been studied. In this paper, we aligned the target sequence with other Sfp-type PPTases, constructed a deletion mutant using the method of double homologous recombination, investigated the biological phenotypes, and compared the intracellular survival and virulence of the mutant and wild-type strains. Additionally, we performed RNA-seq and analyzed the transcription data. The results indicated that the PPTase of P. plecoglossicida shares the highest sequence similarity with PapcpS of P. aeruginosa . A conditional mutant was successfully constructed when pET22b-entD was present. Compared to the wild-type strain, the mutant was lysine indispensable, exhibited poorer growth during the late log phase, was more sensitive to H 2 O 2 exposure, displayed lower siderophore activity, and exhibited a significant reduction in total fatty acid synthesis. Furthermore, fewer bacterial cells of the mutant persisted in mouse macrophage J774A.1, and its toxicity to the host fish was substantially attenuated. RNA-seq analysis revealed 179 differentially expressed genes (DEGs), including 105 up-regulated and 74 down-regulated genes. Genes involved in iron transportation, oxidative stress response, and ABC transporters were down-regulated, while genes in the type III and type VI secretion systems were predominantly up-regulated. The transcriptomic results are consistent with the phenotypic observations, suggesting that the PPTase is essential for bacterial survival and plays important roles in the pathogenicity process. This is the first paper on the PPTase from P. plecoglossicida .